Fungsi Pamali Melaut Masyarakat Bugis di Kelurahan Lapulu Kota Kendari - Arjunita Saputri, Shinta; Marheni, La Ode; Aisyah, Aisyah; Santi, Wa; Alfisari, Wa Ode; Sukmawati, Andi; Mijaya, Siti; Hardiana, Sitti (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims to identify Pamali in fishing and explain their functions within the Bugis community in Lapulu Subdistrict, Kendari City. The research employs a qualitative approach using observation and open-ended interviews with fishermen and community members. The data were analyzed and interpreted through Bronislaw Malinowski’s functionalist framework to examine how Pamali operates in meeting the livelihood needs of the fishing community. The findings reveal three main Pamali: (1) a prohibition against speaking harshly at sea while fishing, (2) a prohibition against going out fishing on Thursday night (the eve of Friday), and (3) a prohibition against going out fishing when a family member is critically ill or has died. These Pamali function as behavioral guidelines that reinforce caution and safety, regulate communication and interaction on boats, and organize family relations and socio-religious obligations. The study underscores that fishing-related Pamali exist not merely as prohibitions, but as local wisdom that sustains livelihoods and social order among the Bugis fishing community in Lapulu.